Analisa Kualitas Air Fisika dan Kimia di Danau Pampait (Physical and Chemical Water Quality Analysis in Lake Pampait) - Ummi Suraya; Lilia Lilia (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This study aims to determine the water condition of Lake Pampait, KamelohBaru Village, Sebangau District, Palangka Raya City, measured from physical and chemical water quality as a measure of the condition of the water quality in Lake Pampait. The study was conducted for approximately 2 (two) months, namely from June to July 2018. Sampling was carried out in 3 (three) stations, namely inlet (station I), middle section (station II) and outlets (station III). The physical and chemical water quality measurements are carried out directly, namely temperature, brightness, depth, pH (Degrees of Acidity) and DO (Dissolved Oxygen) while indirectly or analyzed in the laboratory are PO4 (Phosphate), NO3 (Nitrate) and NH3 (Nitrate) Ammonia). The results of research on physical and chemical water quality is an average temperature of 23.7 oC. Brightness 28.75 cm, Depth 4.25 m, Degree of Acidity (pH) with an average of 6.03, and Dissolved Oxygen (DO) 2.93 mg/L, Phosphate (PO4), Nitrate (NO3), and Ammonia (NH3) ) 0.932 mg/L, it can be concluded that Lake Pampait can be said to be still not polluted and is still considered good for the life of fish and other aquatic organisms.